How does economic policy uncertainty affect prices of housing? Evidence from Germany - Su, Chi-Wei; Li, Xin; Tao, Ran (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
We test the interaction between housing prices and economic policy uncertainty with controlling for the effect of the interest rate in Germany. A bootstrap rolling-window Granger causality test method is utilized for the purpose of detecting their dynamic relationship, since we find significant structural changes across the full-sample of the time series which should be taken into account to avoid estimation errors, and more importantly to get a more instructive conclusion. We find that even in Germany, where house prices are famous for their stability, a strong bilateral Granger causality still exists after controlling for the interest rate of housing loans. Furthermore, we find that though the impact of economic policy uncertainty on housing prices could be positive or negative, it significantly reduces house price volatility, while house price volatility significantly raises economic policy uncertainty, which suggests that the frequently mentioned volatility spillover effect of uncertainty on the housing market is not explanatory. Our results indicate that when the subject is a pillar industry in the national economy, considering only the volatility spillover effect caused by economic policy uncertainty may be one-sided, and the purpose of policy change may be more worthy of consideration
Argumenta Oeconomica, 2019, Nr 1 (42), s. 131-153
Keywords: economic policy uncertainty; house prices; rolling window; bootstrap; Granger causality